2021
DOI: 10.1103/physrevlett.127.042303
|View full text |Cite
|
Sign up to set email alerts
|

Speed of Sound and Baryon Cumulants in Heavy-Ion Collisions

Abstract: We present a method that may allow an estimate of the value of the speed of sound as well as its logarithmic derivative with respect to the baryon number density in matter created in heavyion collisions. To this end, we utilize well-known observables: cumulants of the baryon number distribution. In analyses aimed at uncovering the phase diagram of strongly interacting matter, cumulants gather considerable attention as their qualitative behaviour along the explored range of collision energies is expected to aid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Our results agree with the simplified estimates of Ref. [21] qualitatively, while quantitatively they indicate a smaller c 2 T and a larger d(ln c 2 T )/d(ln n B ) at the HADES collision energy than originally obtained in [21].…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with the simplified estimates of Ref. [21] qualitatively, while quantitatively they indicate a smaller c 2 T and a larger d(ln c 2 T )/d(ln n B ) at the HADES collision energy than originally obtained in [21].…”
supporting
confidence: 92%
“…The extracted susceptibilities can also be used to improve upon the analysis presented in Ref. [21], where it was shown that the cumulants can be used to estimate the (isothermal) speed of sound as well as its logarithmic derivative with respect to baryon density. To do that one needs to determine the true grand-canonical cumulants of baryon number whereas in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In QCD, the chiral critical point (CP) belongs to the Z(2) universality class; thus, it is expected for the fluctuations to diverge at CP, which makes them useful probes of remnants of critical behavior in the relativistic heavy-ion collisions. It has also been recently argued that at low temperatures and large baryon densities, experimentally measured cumulants may allow for direct measurement of the sound velocity [36].…”
Section: Introductionmentioning
confidence: 99%
“…The study in [30][31][32] shows that c 2 s as a function of charged particle multiplicity dN ch /dη can reveal the dynamics of heavy-ion collision. Recently, in [33] the authors estimate c s as a function of the logarithmic derivative with respect to the baryon density of QCD matter, and try to build a connection with the baryon number cumulants to aid in detecting the QCD critical endpoint.…”
Section: Introductionmentioning
confidence: 99%